Organización contable al “Comercial Vivanco 2” del Sr. Vivanco Ocampo Jandry Robinzon del cantón Marcabelí, periodo del 01 de abril al 30 de junio del 2023. - Lojan Caicedo, Mayely Anai (2024)
The Work of Curricular Integration called Accounting Organization to the " Vivanco 2 Stores" of Mr. Vivanco Ocampo Jandry Robinzon of the canton Marcabelí, period from April 1 to June 30, 2023, was carried out with the purpose of meeting the needs of the company in relation to the registration and organization of its business activities in order to enable it to obtain up-to-date control of the transactions carried out; and, enough and competent information on its economic and financial situation. In order to achieve the proposed objectives, different research methods and techniques were used for the development of this work. In relation to the first objective, a plan and manual of accounts was designed adjusted to the needs and activities of the store, detailing the accounts of Assets, Liabilities, Patrimony, Income, Costs and Expenses with their respective codes, thus facilitating the recording of accounts. After that, carrying out the implementation of the second objective, the accounting process was initiated through the Multiple Account System considered didactically, due to the large number of products handled by the store; on the basis of the compilation and classification of the source documentation, the initial inventory was drawn up by means of the physical verification in order to know all the goods, stocks, rights and obligations held by the trader at the beginning of the period and in this way pass on that information to the Statement of Financial Position, with which, the records of the transactions in the Journal were started making use of Auxiliary Books of Purchases, Sales, Accounts Receivable and Accounts Payable, with this information, the General Ledger was developed, which served as the basis for structuring the Trial Balance and then the Worksheet with the respective adjustments that allowed the Financial Statements, made up of the Statement of Results, Statement of Financial Position, Statement of Cash Flows and its corresponding Explanatory Notes. At the end of the accounting process, sufficient and relevant information was obtained on the economic and financial situation of the company, evidencing that the commercial has obtained in the period a Net Profit of the Period of $1,217.39; an Asset of $82,647.62; a Liability of $3,173,57 and a Patrimony of $79,474.05 information that is significant for the owner since it allows him to make efficient decisions, based on the current reality of the commercial.